Core information set for informed consent to surgery for oral or oropharyngeal cancer: A mixed‐methods study. (21st December 2017) - Main, B.G.; McNair, A.G.K.; Haworth, S.; Rooshenas, L.; Hughes, C.W.; Tierney, P.; Donovan, J.L.; Thomas, S.J.; Blazeby, J.M.
Abstract : Objectives: To develop a core information set for informed consent to surgery for oral/oropharyngeal surgery. A core information set is baseline information rated important by patients and surgeons and is intended to improve patients' understanding of the intended procedure. Design: A mixed‐methods study. Systematic reviews of scientific and written healthcare literature, qualitative interviews and observations, Delphi surveys, and group consensus meetings identified information domains of importance for consent. Setting: A regional head and neck clinic in the United Kingdom. Questionnaire participants were recruited from around the UK. Participants: Patients about to undergo, or who had previously undergone, surgery for oral/oropharyngeal cancer. Healthcare professionals involved in the management of head and neck cancer. Main outcome measures: The main outcome was a core information set. Results: Systematic reviews, interviews and consultation observations yielded 887 pieces of information that were categorised into 87 information domains. Survey response rates were 67% (n = 50) and 71% (n = 52) for patient and healthcare professional groups in round one. More than 90% responded in each group in the second round. Healthcare professionals were more likely to rate information about short‐term or peri‐operative events as important while patients rated longer term issues about survival and quality of life. The consensus‐building process resulted in an agreed core information set of 13 domains plus two procedure‐specific domains about tracheostomy and free‐flap surgery. Conclusion: This study produced a core information set for surgeons and patients to discuss before surgery for oral/oropharyngeal cancer. Future work will optimise ways to integrate core information into routine consultations.